Biggest Super Bowl plays - Bowker, Paul, 1954- (Bowker, Paul, 1954- Best of the Super Bowl., 2019)
Profiles twelve of the most iconic plays in an NFL Super Bowl. Includes photographs, facts and stories, a glossary, and sources for further learning.